Pengaruh Pemanfaatan Video Tracker Terhadap Keterampilan Generik Sains Peserta Didik Pada Pembelajaran Gerak Lurus Beraturan - Febrianti, Fira Rosmaliana; Khoiri, Nur; Patonah, Siti; Setiawan, Didik (Jurnal Penelitian Pembelajaran Fisika, 2023)
Learning that exercises generic science skills will result in students being able to understand concepts in solving problems and other scientific activities, as well as being able to learn independently efficiently. The purpose in this study was to determine the effect of using a video tracker in improving students' generic science skills in learning uniform rectilinear motion. In this study using the One-Group Pretest-Posttest Design. The sampling technique in this study is Non-Probability Sampling. The population of this study were students in class X MIPA SMA Al Fattah Terboyo Semarang. The sample of this research was 28 students in class X MIPA SMA Al Fattah Terboyo Semarang. Data collection techniques in the form of tests and observations. Data analysis techniques in this study were normality test, homogeneity test, gain test and hypothesis testing with paired sample t test. Based on the results of the study, there is an effect of using a video tracker on students' generic science skills in learning uniform rectilinear motion. It is known from the results of the analysis of the calculation of the average value of the pretest-posttest increase of 22.12% and from the observations made by the observer, the average value is 80.88% with very good criteria. From the results of the gain test analysis, a value of 0.37 is obtained in the moderate category. The results of the normality test obtained a significance value of 0.85 0.05, then H0 was accepted and Ha was rejected. And the results of the homogeneity test obtained a significance value of 0.46 0.05, then H0 was accepted and Ha was rejected. Therefore it was concluded that there was a significant influence on students' generic science skills at SMA Al Fattah Terboyo Semarang.Keywords: Tracker, Science Generic Skills, GLB.